STABILITY OF STATICALLY INDEFINITE PHYSICALLY NONLINEAR TIMBER STRUCTURAL SYSTEMS - Dubrakova, Ksenia Olegovna (Journal of Applied Engineering Science, 2019)
The procedure for determining the critical stability parameters of wood constructive systems is given, taking into account the features of the deformation stage in which the compressed elements are located. The dependence of critical parameters on the loading scheme and frame dimensions is determined. The order and results of experimental studies of a single-span structural system of wood are given. It was revealed that taking into account the features of the deformation stage, in which the compressed frame racks are located, will lead to an increase in the critical force value. It is concluded that the proposed criterion for assessing the stability of compressed wood core elements makes it relatively easy to assess the resource resistance of such elements, taking into account the effect of the level of operating stresses on the stiffness value.